EMOTIONAL FORMATION, SPIRITUALITY, AND TEACHER-STUDENT RELATIONSHIPS AMID DIGITAL CULTURE IN LEARNING AQIDA AND MORALS - Ruqoyyah Nafisah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aims to gain an in-depth understanding of how Madrasah Tsanawiyah empowers its students to maintain emotional and spiritual control amidst the hustle and bustle of digital culture. The study focuses on the central role of teacher-student relationships in Aqidah Akhlak learning. Using a qualitative case study approach at MTs Nurul Jadid, we collected real stories and experiences from teachers, principals, counselors, and students through interviews, observations, and documentation. Our findings reveal that instilling morals is not solely dependent on material resources, but rather on the interpersonal relationships between teachers and students, which are characterized by empathy and exemplary behavior. This authentic relationship is key to activating spiritual awareness, ultimately enabling students to resist the negative influences of social media. The conclusion emphasizes that students' consciences will be nurtured if teachers are fully present. A warm relationship is a prerequisite for the teachings of Aqidah Akhlak to take hold, creating a generation that is intelligent and has a stable, responsible character.